The Role of Family Empowerment and Welfare in Rimba Sekampung Urban Village as the Frontline in Addressing Sexual Violence and Bullying - Dewi Jannah; Erinaldi Erinaldi; Annisya Rahmadani; Erika Yusmaini (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2023)
The increasing incidence of sexual violence and bullying against children and adolescents has become a serious social problem that requires active involvement from all elements of society, particularly families. This community service program aims to strengthen the role of the Family Welfare Empowerment (PKK) organization in Rimba Sekampung Sub-district as the frontline in preventing and addressing sexual violence and adolescent bullying. The methods applied include socialization and persuasive educational approaches through counseling sessions, interactive discussions, and case consultations involving PKK members as community partners. The results indicate an improvement in participants’ knowledge, awareness, and social sensitivity regarding the forms, causes, and impacts of sexual violence and bullying among adolescents. Furthermore, the program enhances the capacity of PKK members to foster family resilience and create a safe, harmonious, and value-based family environment to support sustainable child and adolescent protection.